GENDER REPRESENTATION IN KOREAN DRAMA WEIGHT LIFTING FAIRY KIM BOK JOO AND STRONG WOMAN DO BONG SOON (World Bulletin of Social Sciences, 2023)
The purpose of this research was to conduct an analysis of the portrayal of women and men in Korean drama films. In order to have a better understanding of this subject matter, we will be looking at it through the lenses of representation theory, content analysis, and the media. The research subject of this study was comprised of 16 episodes of a Korean drama series and 16 episodes of using a qualitative approach together with a descriptive paradigm. Both sets of episodes were analyzed. The method of analysis that is employed is called content analysis. The findings demonstrated that gender was represented in a variety of ways in the Korean drama films that were recognized by the researchers using the three theories that they employed as well as the semiotic approach. Additionally, the findings demonstrated that the semiotic approach contributed to the analysis of these representations